Studi Literatur: Audit Tata Kelola Teknologi Informasi Berbasis Framework Cobit 5 - Afandi Afandi; Kartika Pradana Suryatimur; Masculine Muhammad Muqorobin (International Forum of Researchers and Lecturers, 2024)
The advancement of information technology in the era of society 5.0 has made it an inseparable thing, including in an organization. In reality, organizations in implementing information technology still experience many problems, such as lack of information technology governance measurement, low risk management, and vulnerabilities in system security. Therefore, making various organizations compete to provide optimal services so that it is necessary to conduct an information technology governance audit as evaluation material. Framework COBIT 5 is one of the frameworks that can be used to conduct an organizational information technology governance audit. The writing method used is literature review both from books and journals related to the COBIT 5 framework. The purpose of this writing is to provide an overview and show the advantages and disadvantages of the COBIT 5 framework. Based on the results of the analysis carried out, it is necessary to make improvements to information technology governance in each organization to achieve the desired capabilities. An information technology governance audit of the organization can provide evaluations and recommendations for improvement so that it can improve information services from the organization.